“The Modulation of Platelets’ Activity is Associated with Early Onset of Anxiety Traits in Adolescents” - Kalpna Verma; Dileep K Verma; Anupma Verma; Vandana Ranjan (The Bioscan, 2026)
Platelets, which share serotonergic pathways with the CNS, offer a unique insight into peripheral responses during anxious behaviour processing. Serotonin, released from active platelets, is known for playing a central role in autonomic and emotional regulation of complex biochemical pathways including those associated with undesired behavioural outcomes of clinical significance, as in the case of anxiety.